PENGARUH PERSEPSI KUALITAS, CITRA MEREK DAN PERSEPSI NILAI TERHADAP KEPUASAN UNTUK MENINGKATKAN LOYALITAS PELANGGAN (Studi Pada Produk Laptop Merek Asus) - Paramitha, Komang Ayu Indah; Kusuma, A.A Gede Agung Artha (E-Jurnal Manajemen; Vol 7 No 10 (2018), 2018)
The purpose of this study is to explain the effect of quality perception, brand image and perception of value on satisfaction to improve customer loyalty. This research was conducted in Denpasar City involving 105 respondents through purposive sampling method and data collection was done by distributing questionnaires containing statement related to variable of perception of quality, brand image, perception value, customer satisfaction and customer loyalty. Data analysis technique used is path analysis technique. The results of this study found that the perception of quality, brand image and perception of value have a positive and significant impact on customer satisfaction. Customer satisfaction also has a positive and significant influence on customer loyalty. This shows that improving customer loyalty, the company is expected to maintain and focus on the perception of quality, brand image and value perception, it can increase customer satisfaction so that will increase customer loyalty. Keywords :quality perception, brand image, value perception, customer satisfaction, customer loyalty.